Transcriptome of pleuropodia from locust embryos supports that these organs produce enzymes enabling the larva to hatch - Konopová, Barbora; Buchberger, Elisa; Crisp, Alastair (Frontiers in zoology, 2020)
BACKGROUND: Pleuropodia are limb-derived glandular organs that transiently appear on the first abdominal segment in embryos of insects from majority of "orders". They are missing in the genetic model Drosophila and little is known about them. Experiments carried out on orthopteran insects 80 years ago indicated that the pleuropodia secrete a "hatching enzyme" that digests the serosal cuticle to enable the larva to hatch, but evidence by state-of-the-art molecular methods is missing. RESULTS: We used high-throughput RNA-sequencing to identify the genes expressed in the pleuropodia of the locust Schistocerca gregaria (Orthoptera). First, using transmission electron microscopy we studied the development of the pleuropodia during 11 stages of the locust embryogenesis. We show that the glandular cells differentiate and start secreting just before the definitive dorsal closure of the embryo and the secretion granules outside the cells become more abundant prior to hatching. Next, we generated a comprehensive embryonic reference transcriptome for the locust and used it to study genome wide gene expression across ten morphologicaly defined stages of the pleuropodia. We show that when the pleuropodia have morphological markers of functional organs and produce secretion, they are primarily enriched in transcripts associated with transport functions. They express genes encoding enzymes capable of digesting cuticular protein and chitin. These include the potent cuticulo-lytic Chitinase 5, whose transcript rises just before hatching. Unexpected finding was the enrichment in transcripts for immunity-related enzymes. This indicates that the pleuropodia are equipped with epithelial immunity similarly as barrier epithelia in postembryonic stages. CONCLUSIONS: These data provide transcriptomic support for the historic hypothesis that pleuropodia produce cuticle-degrading enzymes and function in hatching. They may also have other functions, such as facilitation of embryonic immune defense. By the genes that they express the pleuropodia are specialized embryonic organs and apparently an important though neglected part of insect physiology.
Keywords: Gland; RNA-seq; Embryo; Immunity; Ecdysone; Moulting fluid; Orthoptera; Appendage; Cuticle; Schistocerca gregaria